Analisis Yuridis Terhadap Pertimbangan Hakim Atas Pemberhentian PNS Oleh Gubernur Kalimantan Timur Dalam Putusan Nomor 34/G/2020/PTUN.SMD - Elviandri; Fiqri Abdillah; Bayu Prasetyo (CV Rewang Rencang, 2025)
This study examines the judicial considerations in Decision Number 34/G/2020/PTUN.SMD concerning the annulment of the Governor of East Kalimantan’s decree dismissing a civil servant. The analysis reveals procedural and substantive defects, as the decision failed to comply with statutory regulations and the General Principles of Good Governance. The Administrative Court declared the decree null and void, restoring the plaintiff’s rights as a civil servant. The findings highlight the role of the Administrative Court as a judicial control mechanism over public officials’ actions while reinforcing legality, accountability, and good governance in public administration.